Reversibility and Low Commitment to Forward Catalysis in the Conjugation of Lipid Alkenals by Glutathione Transferase A4-4 - Michele Scian; Lorela Paço; Taylor A. Murphree; Laura M. Shireman; William M. Atkins (Biomolecules, 2023)
High concentrations of electrophilic lipid alkenals formed during oxidative stress are implicated in cytotoxicity and disease. However, low concentrations of alkenals are required to induce antioxidative stress responses. An established clearance pathway for lipid alkenals includes conjugation to glutathione (GSH) via Michael addition, which is catalyzed mainly by glutathione transferase isoform A4 (GSTA4-4). Based on the ability of GSTs to catalyze hydrolysis or retro-Michael addition of GSH conjugates, and the antioxidant function of low concentrations of lipid alkenals, we hypothesize that GSTA4-4 contributes a homeostatic role in lipid metabolism. Enzymatic kinetic parameters for retro-Michael addition with trans-2-Nonenal (NE) reveal the chemical competence of GSTA4-4 in this putative role. The forward GSTA4-4-catalyzed Michael addition occurs with the rapid exchange of the C2 proton of NE in D2O as observed by NMR. The isotope exchange was completely dependent on the presence of GSH. The overall commitment to catalysis, or the ratio of first order kcat,f for ‘forward’ Michael addition to the first order kcat,ex for H/D exchange is remarkably low, approximately 3:1. This behavior is consistent with the possibility that GSTA4-4 is a regulatory enzyme that contributes to steady-state levels of lipid alkenals, rather than a strict ‘one way’ detoxication enzyme.